Investigation of the use of solar cells of thin film in the cover of an office building = Investigación del uso de celdas solares de película delgada en la cubierta de un edificio de oficinas - Guerrero, Doris; Pavón, Cristina; Tendero Caballero, Ricardo (Building & Management, 2020)
AbstractThis document presents an analysis of the incorporation of a thin-film solar cell system, applied to a building to provide greater energy production under diffuse radiation, homogeneous integration that minimizes the costs of raw material for installation. The intervention area is located on the roof slab and terraces within the Rehabilitation of the office building located in Apolonio Morales Street nº29 in Madrid, with a total area of 78. 17 m2 distributed in three sectors. The objective of this work is to generate, through research and techno-logical development, systematic knowledge that contributes to the analysis of a light, solar technology that provides versatility in design and simplifies installation costs compared to traditional photovoltaic systems. In such a way that there is an energy saving without it modifies the aesthetics of the building in walkable areas of terrace and deck slab. The costs of this system surround the traditional ones, assuming a feasible renewable energy alternative with the capacity to return the investment in less than 3 years.On the other hand, it is intended that the results of this work serve to analyze the possible applications of this technology in Ecuador, where less than 1% of the population has access to renewable or non-polluting energyResumenEl presente documento analiza la incorporación de un sistema de célula solar de película delgada en una edificación, para aportar una mayor producción de energía bajo radiación difusa de integración homogénea, que minimiza los costos de materia prima para su instala-ción. El área de intervención está situada en la losa de cubierta y terrazas dentro de la Rehabilitación del edificio de oficinas ubicado en la calle de Apolonio Morales nº29 de Madrid, con un área total de 78.17 m2 distribuidas en tres sectores. El objetivo de este estudio es generar a través de la investigación y el desarrollo tecnológico, conocimiento sistemático que contribuya con el análisis de una tecnología solar ligera que proporcione versatilidad en el diseño y simplifique los costos de instalación frente a los sistemas tradicionales fotovoltai-cos. De tal manera que se produzca un ahorro de energía sin que esta modifique la estética del edificio en áreas transitables de terraza y de losa de cubierta. Los costes de este sistema son similares a los tradicionales, suponiendo una alternativa de energía renovable factible con capacidad de retorno de la inversión en menos de 3 años.Por otro lado, se pretende que los resultados de este trabajo sirvan para analizar las posibles aplicaciones de esta tecnología en el Ecua-dor, donde menos del 1 % de la población tiene acceso a energías renovables o no contaminantes.